Type 2 diabetes mellitus and neurodegenerative disorders: The mitochondrial connection - Isabella R. Baduini; Jose E. Castro Vildosola; Sheida Kavehmoghaddam; Fatmanur Kiliç; S. Aiman Nadeem; Juan J. Nizama; Marietta A. Rowand; Dileep Annapureddy; Chris-Ann Bryan; Lisa H. Do; Samuel Hsiao; Sai A. Jonnalagadda; et al. (Elsevier, 2024)
The incidence of type 2 diabetes mellitus (T2DM) has increased in our society in recent decades as the population ages, and this trend is not expected to revert. This is the same for the incidence of the main neurodegenerative disorders, including the two most common ones, which are, Alzheimer's and Parkinson's disease. Currently, no pharmacological therapies have been developed to revert or cure any of these pathologies. Interestingly, in recent years, an increased number of studies have shown a high co-morbidity between T2DM and neurodegeneration, as well as some common molecular pathways that are affected in both types of diseases. For example, while the etiopathology of T2DM and neurodegenerative disorders is highly complex, mitochondrial dysfunction has been broadly described in the early steps of both diseases; accordingly, this dysfunction has emerged as a plausible molecular link between them. In fact, the prominent role played by mitochondria in the mammalian metabolism of glucose places the physiology of the organelle in a central position to regulate many cellular processes that are affected in both T2DM and neurodegenerative disorders. In this collaborative review, we critically describe the relationship between T2DM and neurodegeneration; making a special emphasis on the mitochondrial mechanisms that could link these diseases. A better understanding of the role of mitochondria on the etiopathology of T2DM and neurodegeneration could pave the way for the development of new pharmacological therapies focused on the regulation of the physiology of the organelle. These therapies could, ultimately, contribute to increase healthspan.